Community College Finances and International Student Enrollment (Comparative & International Education Series, 2021)
Chapter 5|16 pages Community College Finances and International Student EnrollmentBy Ji Yeon Bae, Manuel S. González CanchéDespite the prevalence of international students in US community colleges, little is known about how international student enrollment affects this sector. We used institutional-level and county-level data on community colleges and panel regression techniques to examine the relationship between international student enrollment and institutional finances. Specifically, using fixed-effects panel regression models, we tested the associations between public sources of funding and international student enrollment as well as that between international student enrollment and tuition revenue. We found that although a subset of institutions has enrolled a high number of foreign students, the sector as a whole still retains its local nature, as evidenced in the weak relationships between the number of international students and institutional finances.